Computer simulation of high-current ion bunches transport and acceleration with additional space charge compensation by thermal electrons - Manuilenko, O.V.; Karas, V.I. (Вопросы атомной науки и техники, 2014)
The particle in cell simulation results, within the limits of the complete set of the Maxwell-Vlasov equations, of the short (the ion bunch length is much smaller than the cusp length) and long (the ion bunch length is much longer than the cusp length) high-current compensated tubular ion bunches transportation and acceleration in the peaked fence magnetic field are presented. The ion bunch current, at injection in the cusp, is compensated by an accompanying electron bunch. Additional compensation of the ion bunch space charge by means of thermal electrons generated in the drift space has been studied. It is shown that both for short and for long ion bunches, the optimized additional space charge compensation by thermal electrons leads to a reduction of the energy spread of the accelerated ion beam at the output of the cusp. Приведены результаты численного моделирования методом макрочастиц в рамках полной системы уравнений Власова-Максвелла, транспортировки и ускорения коротких (длина ионного сгустка значительно меньше длины каспа) и длинных (длина ионного сгустка значительно больше длины каспа) сильноточных трубчатых ионных сгустков в магнитном поле остроугольной геометрии. Ток ионного сгустка при инжекции в касп скомпенсирован сопровождающим электронным сгустком. Изучена дополнительная компенсация объемного заряда ионного сгустка тепловыми электронами. Показано, что как в случае коротких, так и в случае длинных ионных сгустков оптимизированная дополнительная компенсация объемного заряда тепловыми электронами приводит к уменьшению энергетического разброса ускоряемого ионного пучка на выходе из каспа. Наведено результати числового моделювання методом макрочасток у рамках повної системи рівнянь Власова-Максвелла, транспортування та прискорення коротких (довжина іонного згустка значно менше довжини каспа) та довгих (довжина іонного згустка значно більша за довжину каспа) сильнострумових трубчастих іонних згустків у магнітному полі гострокутової геометрії. Струм іонного згустка при інжекції в касп, скомпенсовано електронним згустком. Досліджено додаткову компенсацію об'ємного заряду іонного згустка за допомогою теплових електронів. Показано, що як у випадку коротких, так і у випадку довгих іонних згустків додаткова оптимізована компенсація об'ємного заряду тепловими електронами призводить до зменшення енергетичного розкиду іонного пучка, який прискорюється на виході з каспа.